Performance Test of Input Mechanisms on Cardboard Folding Machine System - Pasha, Mohraffi Azura; Oktaviandri, Muchamad; Martana, Budhi (ROTASI, 2024)
The packaging industry has experienced significant global growth, driven by increasing demand for cardboard packaging and the rising volume of packaging waste. This growth highlights the industry's need to enhance efficiency and effectiveness in production processes. Manual handling of cardboard sheets for folding and stacking is time-consuming, necessitating the development of automated solutions. This study introduces the cardboard folding machine, designed and fabricated by mechanical engineering students at UPN Veteran Jakarta. The machine comprises three main mechanisms: the input mechanism, the conveyor for folding cardboard sheets, and the output mechanism. To optimize production, performance testing is conducted to identify the most efficient speed settings to achieve maximum cardboard folding output. This testing also aims to promote the machine as a practical tool for potential users in the packaging industry. Previous research has explored various mechanisms for handling cardboard, including friction systems, slider systems, and vacuum systems. Each approach offers distinct advantages and challenges. By addressing these issues, the cardboard folding machine aims to improve production reliability in alignment with the needs of potential users. The results of this study delineate the advantages and disadvantages inherent to both friction and slider mechanisms. These results can be utilized to tailor the mechanisms according to the preferences of prospective users.